Socio-demographic profile of Human Immunodeficiency Virus patients on second line antiretroviral therapy in a tertiary care centre of North-East India - Karmakar, Arun; Mazumdar, Abhipsa; Karmakar, Nabarun; Mishra, Aditya Kumar (International Journal of Research in Medical Sciences, 2019)
Background: HIV/ AIDS is one of the major global health issue, resulting an epidemic. Understanding the socio-demographic profile with magnitude of risky behavior might include positive messages in the routine HIV/AIDS care and treatment. Objective of this study was to find out the socio-demographic, behavioural characteristics among patients receiving second line ART (Anti-Retroviral therapy) in a tertiary centre of North-East India. Methods: A cross sectional study was carried out among 90 PLWHA patients receiving second line ART in Regional Institute of Medical Sciences (RIMS), Imphal from March 2016 to August 2017. A predesigned and pretested schedule was used as study tool to collect required information. Results: Majority participants (43.3%) belonged to 30-40 years age group, mean age 39.96±8.021 years; 51.1% were female. Majority (58.9%) got infected with HIV through heterosexual route followed by IV drug use (31.1%). Nearly half (51.1%) were diagnosed with HIV for 11-15 years duration and majority (61.1%) were under 2nd line ART for 6-10 years duration. Here, 3.3% subjects had Hepatitis B and 7.8% were infected with hepatitis C. Conclusions: Young population were most affected group and heterosexual route being the commonest mode of transmission. Combination of socio-demographic, behavioural risk factor and unawareness are responsible for rapid spread of HIV/AIDS. So, people need to be educated for primary and secondary prevention.